Religious values-based education then and now (Academic Journal of Internal Affairs, 2024)
Aim: The aim of the article is to show that the state and society cannot be satisfied with punishing the offender, it is in society’s interest to help the offender.Methodology: The introduction of reintegration into criminal law is not an achievement of the 21st century. Scholars have previously expressed their views on the need to reintegrate offenders into society and the methods they believed can achieve this. Many of them have identified religious education of offenders as the most effective means.Findings: The paper brings together previous initiatives and compares them with current penal policy and the objectives set out in the Penal Code.Value: Research along similar values and goals connects the past with the present and the future. Humanistic criminal law always expects offenders to maximise their chances of living a life in accordance with social norms, both during and after the execution of their sentence.
Keywords: reintegration; offender; religion; education